Investigation of minor groove binders (MGB), non-ionic surfactant vesicles (NIV) delivery systems and IL-4i1 as novel pathogen- and host-directed drug therapy for tuberculosis - Hlaka, Lerato (Division of Immunology, 2020)
Tuberculosis (TB), caused by Mycobacterium tuberculosis is the leading infectious disease epidemic that claims over 1.6 million lives, while 10 million fell ill in 2017. South Africa is burdened with the third highest global incidences following India and China with high rates of co-infections with HIV and highest numbers of multi-drug resistant (MDR) and extremely resistant (XDR) TB per capita. The current treatment regimen is decades old and requires a prolonged period of 6 months. The lack of efficient TB therapy and the emergence of MDR and XDR TB, there is an urgent need to find new drug targets for TB therapy through understanding the complex host-pathogen interactions. This may then lead to pathogen, host-directed therapies (HDT) or adjunct therapies as well as the development of effective drugs and drug formulations for the treatment of TB. Here we aimed to investigate potential targets for pathogen-and host-directed therapies for TB. We screened the anti-mycobacterial activity of 172 minor groove binder (MGB) compounds that selectively bind to AT-rich regions of the minor groove of bacterial DNA with the helical structure matching that of DNA in Mtb culture. Of the 172 total compounds screened 17 hits were identified, of which 2, MGB 362 and MGB 364 displayed intracellular mycobactericidal activity against Mtb HN878 at an MIC50 of 4.09 and 4.19 μM, respectively, whilst being non-toxic. Encapsulation of MGBs into non- ionic surfactant vesicles (NIVs) demonstrated a 1.6- and 2.1-fold increased intracellular mycobacterial activity, similar to that of rifampicin when compared with MGB alone. Treatment with MGB 364 or MGB 364 formulation did not cause DNA damage in murine infected macrophages as displayed by low expression of γ-H2Ax compared to H2O2 and DMSO. Intranasal administration of MGB 364 and MGB-NIV 364 formulation showed one log reduction in bacterial burden with improved pathology and immune cytokine production when in formulation. However, intranasal administration of 10 mg/kg MGB 362 together with rifampicin had no effect on bacterial loads. In summary, the data demonstrate the potential of MGB as a novel class of drug/chemical entity in anti-TB therapy and NIVs as an effective delivery system in a novel anti-TB formulation. Using deep CAGE and small RNA (CHIP-seq) technologies, International Center for Genetic Engineering and Biotechnology’s Cytokines and Diseases lab in collaboration with the RIKEN Center for Integrative Medical Sciences (Yokohama, Japan) performed a novel transcriptomics study approach by conducting a genome-wide transcriptional analyses of RNA transcripts from classically activated macrophages (caMph) and alternatively activated macrophages (aaMph) during Mtb infection. We identified host target genes that may play a role in host immune subverting mechanism by Mtb to hide away from host effector functions providing a possible target for host-directed therapy for tuberculosis. It is postulated that Mtb modulates the transcriptional landscape of IL-4/IL13 alternatively activated macrophages (aaMph) to escape killing by reactive nitrogen intermediates (NO) and reactive oxygen species (ROS) functions by IFN-γ stimulated classically activated macrophages (caMph). Here we report on the immunoregulatory role of IL-4i1, a candidate gene that was upregulated in aaMph during Mtb infection. IL-4i1 is a secreted L-amino oxidase with antibacterial properties. The enzyme converts Phenylalanine (Phe) into phenylpyruvate releasing toxic products ammonia and hydrogen peroxide (H2O2) which in-turn cause immunosuppression of effector T-cells by directly inhibiting polarization, proliferation and function or by promoting the generation of Foxp3 T-regulatory cells. Thus suggesting that IL-4i1 is involved in immune-regulatory mechanisms and may be implicated in immune evasion mechanisms by the pathogen. Here we report on the role of IL-4i1 on tissue localized T-cell activation and proliferative status thus maintaining immune local immune homeostasis. Thus showing that the absence of IL-4i1 could cause autoimmunity. To determine the functional role of IL-4i1 during Mtb infection, IL-4i1 deficient mice and wild-type littermate controls were infected with H37Rv and hypervirulent HN878 Mtb strain. IL-4i1 deficient mice were highly resistant to both strains of Mtb at 12- and 21-days post-infection as denoted by significant reduction in bacterial loads, reduced inflammation, reduced tissue iNOS expression reduced recruitment of interstitial macrophages, pro-inflammatory cytokines showed a trend for reduction. Interestingly there was a significant increase in NO production in infected tissues. There was an increase in M1-like macrophages that correlated with increased pro-inflammatory cytokines and chemokines. These data suggested that IL-4i1 regulates macrophage-mediated inflammatory responses during acute Mtb infection thus showing potential as an immunomodulatory target for TB HDT therapy. The study thus provides a framework for new drug targets for the development of new effective drugs and vaccines for TB therapy.